An Analysis of Perceptions of the Relationship Between the Athletic Director and Athletics’ Direct Reports in NCAA Division II - Kelly P Elliott; Beth Johansen; Amanda M Siegrist (Journal of Applied Sports Management, 2023)
The roles and responsibilities of the individual designated as the athletics’ direct report (ADR) on NCAA Division II member institution campuses are not clearly defined. The absence of clear guidelines creates the opportunity for differences in the relationships between the athletic director (AD) and the designated ADR between peer institutions. The purpose of this study was to explore the current relationship between ADs and ADRs and analyze current practices. Results indicated positive relations between ADs and ADRs on campus and that communication is key to a successful relationship. Recommendations for practitioners are discussed.
Keywords: Athletics’ Direct Report; collegiate athletics; administration; NCAA